The access to justice of victims in the context of COVID-19 - Chávez Matos, Ana María (2021)
This article studies the various problems faced by victims in accessing justice in the context of the health emergency caused by COVID-19. It shows the great importance and practical usefulness of the 100 Brasilia Rules in the treatment and accompaniment of the victim during the work carried out by the Public Prosecutor’s Office to defend their violated rights. It mentions the challenges posed by the imposition of quarantine at the institutional level. Also, the consequences of quarantine, for example, the increase in the number of victims among the vulnerable population.